Heat Capacity of Layered Perovskite Compounds: EsBaCuFeO5 (Es = Ho, Gd, and Yb). Issue 11 (6th July 2022) - Koç, Hüseyin; Bölükdemir, Mustafa Hicabi; Eser, Erhan
Abstract : The layered perovskite compounds, which show multiferroic properties, have attracted interest due to their interesting magnetic and electronic properties. Herein, the heat capacity of EsBaCuFeO5 (Es = Ho, Gd and Yb) as a function of the temperature using the overall equation of fitting is investigated. The Debye temperature, Einstein temperature, the coefficients m and γ are derived by fitting experimental heat capacity data with the overall equation of fitting that consists of the contribution from electronic, Debye, and Einstein terms. The values of the fitting parameters obtained are in good agreement with the results in the literature. The results display that the method can be used for calculation of the heat capacity of the layered perovskite compounds over the entire range of temperature. Abstract : Herein, the heat capacity of GdBaCuFeO5 is calculated by using the fitting equation that consists of the contribution from electronic, Debye and Einstein terms. The results agree well with the available literature data. The deviations observed below 30 K can be eliminated by adding the effect of crystalline electric field on the rare earth ions.